Development and Evaluation of a Semi-Nested PCR Method Based on the 18S ribosomal RNA Gene for the Detection of Babesia aktasi Infections in Goats - Ulucesme, Mehmet Can; Ozubek, Sezayi; Aktas, Munir (Mdpi, 2024)
Simple Summary We developed a new test to detect Babesia aktasi, a parasite that infects goats, using a method called semi-nested PCR. This method focuses on a specific part of the parasite's DNA to ensure accuracy. We checked the test against several other similar parasites to make sure it only detected B. aktasi, which it did successfully. To see how sensitive our test is, we used blood samples with known amounts of the parasite and found that our test could detect even very low levels of infection. Our results show that this new test is both highly accurate and sensitive, making it a valuable tool for identifying B. aktasi infections in goats. This new PCR method provides a reliable tool for detecting B. aktasi in goats, which is crucial for managing and preventing the spread of this infection, ultimately protecting goat health and improving agricultural productivity.Abstract We developed and evaluated a semi-nested PCR assay for the detection of Babesia aktasi infection in goats based on the sequence of the B. aktasi 18S ribosomal RNA gene. Following in silico screening, the specificity of the primers was assessed using reference DNA samples, including B. ovis, B. motasi, B. crassa, B. venatorum, B. divergens, B. capreoli, Theileria ovis, and T. annulata. To determine the sensitivity of the method, blood infected with 2% parasitemia of B. aktasi was diluted to 10-fold serial dilutions. The method specifically amplified a 438 bp fragment of B. aktasi DNA, but did not demonstrate cross-amplification with the other hemoparasites tested. The sensitivity assay indicated that this PCR method was able to detect infection at a dilution of 10-8 of 2% parasitemia (0.074 parasites/200 mu L). Ninety-seven blood samples collected from goats were used to analyze for B. aktasi, and the infection was detected in 18.5% of the goats. Additionally, the method was also applied to 44 field DNA samples that were detected to be positive for B. aktasi by reverse line blotting (RLB), and showed 84.1% agreement. The findings revealed that newly developed semi-nested PCR can detect B. aktasi infections in goats with high sensitivity and specificity.
Keywords: Babesia aktasi; goats; semi-nested PCR; specific primers; 18S ribosomal RNA gene